PERBAIKAN SISTEM KERJA PADA DIVISI PACKING PRODUK RACK TROLLEY DENGAN METHOD TIME MEASUREMENT (MTM) - Khoir, Muhammad Fathul; Fudhla, Ahmad Fatih; Santoso, Gempur (JISO : Journal of Industrial and Systems Optimization, 2021)
The work system is the most important thing in the company, especially in manufacturing companies that produce various kinds of kitchen utensils made from stainless steel 402 and stainless steel 201 according to market demand. Of the many existing products, there are products with the highest demand level but take a long time in the packing division, which only has one station. The MTM (Method Time Measurement) method is used to map work movements that focus on work elements in the packing division with mobile gastronomic rack trolley observation products. After observing and measuring, this division has two light work elements but the processing time is quite long, the sandpaper work element is 9.48 minutes with the clean lab work element 8.13 minutes so that in total there are 9 work elements with a time of 53 minutes, by combining the sandpaper and lab work elements. clean with rework mapping, the result is 9.97 minutes and there is a balance of workload between right-hand movement and left-hand movement, from combining these elements, the work element in the packing division becomes more maximal, namely 8 work elements with 37 minutes per product.